Tax incentives and corporate borrowing: Evidence from finnish company panel data - Kimmo Virolainen (Bank of Finland, 1998)
This study analyses the relationship between taxes and corporate borrowing decisions, both theoretically and empirically.A dynamic stochastic model that allows for interactions between the firm's investment and financial decisions is constructed and its properties are examined.It is shown that corporate tax exhaustion may yield an internal financial optimum for the firm without the need to resort to institutional borrowing constraints.The comparative static results with respect to the firm's optimal debt level remain mostly indeterminate due to conflicting income and substitution effects, but it is possible to prove analytically that firms' borrowing responses to changes in a key tax incentive variable, the available nondebt tax shields, should vary according to their profitability.This result is also confirmed by a simulation analysis. In the empirical work, the borrowing behaviour of Finnish companies is analysed, both descriptively and econometrically over the period 1978-1991.The descriptive analysis reports financing and investment patterns of Finnish companies and
URN:NBN:fi:bof-201408071717
Keywords: 330